Diagnosing the Typology of the Human Psyche in the Qur’an: A Study of the Salim, Muqtashid, and Maridh Souls - Nurusshobah, Nurusshobah; Wahid, Ilham Dhya'ul; Aini, Hafizatul (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2025)
This study aims to examine the typology of the human psyche in the Qur'an, focusing on three principal categories of the soul: salīm, muqtasid, and marīd. Employing a thematic approach to relevant Qur'anic verses, the research analyzes how the Qur'an portrays the inner states of the human soul and offers a conceptual foundation for understanding and addressing psychological challenges. The study is conducted through library research using a thematic exegesis (tafsīr) approach, complemented by an exploration of the views of both classical and contemporary scholars regarding the Qur'anic construction of human psychology. The findings reveal that the salīm soul is described as pure, free from polytheism, and firmly rooted in monotheism, representing the ideal state of spiritual wholeness. The muqtasid soul occupies a moderate position, symbolizing individuals who strive to balance purity and deviation a type particularly relevant in contemporary social contexts. Meanwhile, the marīd soul reflects a disturbed psychological condition caused by doubt, hypocrisy, or destructive desires, which the Qur'an addresses comprehensively through spiritual purification (tazkiyah al-nafs), the strengthening of faith, and psychospiritual therapy. This study highlights that the Qur'anic classification of the soul is not merely theoretical but also practical, offering both preventive and curative solutions to the moral and spiritual crises of modern society, and contributing to the advancement of Islamic psychology and character education. Penelitian ini bertujuan menguraikan tipologi kejiwaan manusia dalam Al-Qur’an dengan menitikberatkan pada tiga kategori pokok jiwa, yaitu salīm, muqtasid, dan marīd. Dengan pendekatan tematik terhadap ayat-ayat terkait, kajian ini menelaah bagaimana Al-Qur’an memaparkan dinamika batin manusia dan menyediakan kerangka konseptual dalam memahami serta mengatasi persoalan psikologis. Penelitian dilaksanakan melalui studi kepustakaan dengan metode tafsir tematik (tafsīr maudhū‘ī), disertai telaah atas pandangan ulama klasik dan kontemporer mengenai konstruksi psikologi Qur’ani. Hasil kajian menunjukkan bahwa jiwa salīm digambarkan sebagai jiwa yang suci, bersih dari syirik, dan teguh dalam ketauhidan, mencerminkan kondisi ideal kematangan spiritual. Jiwa muqtasid berada dalam posisi tengah, mewakili individu yang berusaha menyeimbangkan antara kesalehan dan penyimpangan, sehingga relevan untuk konteks sosial modern. Adapun jiwa marīd menunjukkan kondisi kejiwaan yang terganggu oleh keraguan, kemunafikan, atau dorongan negatif, yang ditangani Al-Qur’an secara menyeluruh melalui pemurnian jiwa (tazkiyah al-nafs), penguatan iman, serta pendekatan terapi psiko-spiritual. Kajian ini menegaskan bahwa klasifikasi jiwa dalam Al-Qur’an bersifat aplikatif sekaligus konseptual, memberikan solusi preventif dan kuratif atas krisis moral-spiritual masa kini, serta mendukung pengembangan psikologi Islam dan pendidikan karakter.